Comparison of mucolytic pharmacological efficacy between some generic and branded herbal pharmaceutical preparations in vitro - بلال لؤي; زينة حمامة; ديما محمد (Latakia University Journal -Medical Sciences Series, 2024)
Generic medicines are widely used as alternative drugs to branded drugs, including herbal drugs used to treat respiratory diseases, which are becoming increasingly popular as a natural alternative with less harmful effects compared to chemically synthesized drugs. Most patients resort to generic drugs considering the high cost of drugs especially branded drugs as they cannot afford treatment with branded drugs, in addition to its wide spread in local pharmacies. The research aims to compare the effectiveness of generic mucolytic plant preparations with the same branded preparations available in the Syrian local market. The in vitro comparison was done between both ivy and wild thyme preparations on a synthetic sputum media, and the study included two commercial products for each plant type. The study concluded that both of branded ivy preparations and thyme preparations are superior to generic preparations.